Using consulting systems : business skills - Reed, Thomas (Info-line (Washington, D.C.), 2003)
Using Consulting Systems describes how to initiate and develop relationships with prospective clients. The organizational systems model is an analytical tool that helps consultants gain a holistic view of issues and problems. Problem-solving tools simplify developing alternative solutions and helping clients choose the best one for their particular circumstances.